PENGARUH LEADERSHIP STYLE TERHADAP FINANCIAL PERFORMANCE DENGAN VARIABEL INTERVENING EMPLOYEE SATISFACTION DAN CUSTOMER SATISFACTION PADA SEKTOR PERBANKAN DI SURABAYA - Novitasari Purwanto; Devie Devie (Business Accounting Review, 2016)
The purpose of this study was to know whether there was significant affect ofLeadership Style towards Financial Performance with Employee’s Satisfaction andCustomer’s satisfaction as intervening variables in banking corporate in Surabaya.Employee’s Satisfaction and Customer’s Satisfaction were used as an interveningvariables to see the affect of Leadership Style to Financial Performance. The sampleused in this study was banking corporates listing in Bursa Efek Indonesia (BEI) thatgenerate profit in the last 3 years. The data analysis used Partial Least Squaremethod with 600 respondents from 30 selected banks in Surabaya. The result of thisstudy showed that Leadership Style had positive affect on Financial Performance.